2017
DOI: 10.1515/revneuro-2017-0008
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting nicotine’s role in the ageing brain and cognitive impairment

Abstract: AbstractBrain ageing is a complex process which in its pathologic form is associated with learning and memory dysfunction or cognitive impairment. During ageing, changes in cholinergic innervations and reduced acetylcholinergic tonus may trigger a series of molecular pathways participating in oxidative stress, excitotoxicity, amyloid-β toxicity, apoptosis, neuroinflammation, and perturb neurotrophic factors in the brain. Nicotine is an exogenous agonist of nicotinic acetylcholi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 161 publications
(183 reference statements)
0
26
0
Order By: Relevance
“…Nicotine distributes to the brain shortly after peripheral administration (whether intraperitoneal, intravenous, oral, or subcutaneous) with maximum between 30 and 60 min, and can be detected in the CNS as late as 4 h after injection (Crooks and Dwoskin, 1997). In contrast to distribution after peripheral administration, smoking causes nicotine to massively distribute to the bloodstream and from there to the brain in 10–20 s (Majdi et al, 2017). Due to the prominence of the base and associated lipid solubility, nicotine readily penetrates the blood-brain barrier (BBB) at physiological pH (Oldendorf et al, 1979; Tega et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nicotine distributes to the brain shortly after peripheral administration (whether intraperitoneal, intravenous, oral, or subcutaneous) with maximum between 30 and 60 min, and can be detected in the CNS as late as 4 h after injection (Crooks and Dwoskin, 1997). In contrast to distribution after peripheral administration, smoking causes nicotine to massively distribute to the bloodstream and from there to the brain in 10–20 s (Majdi et al, 2017). Due to the prominence of the base and associated lipid solubility, nicotine readily penetrates the blood-brain barrier (BBB) at physiological pH (Oldendorf et al, 1979; Tega et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…We also excluded studies that evaluated the effects of nicotine (rather than its metabolites) on the cognitive function. We examined the effects of nicotine in a previous publication (Majdi et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nicotine (NIC) is an alkaloid extracted from Nicotiana tabacum and an exogenous agonist of nAChRs [ 15 ]. Accumulated evidence from animal and clinical studies showed that NIC has cognitive-enhancing effects, improving performance in several domains of cognition, including attention, learning, and working memory [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nicotine is a nAChR agonist and pharmacological chaperone that stimulates cholinergic activity in the brain (Jackson et al, 2010 ; Sadigh-Eteghad et al, 2015a ). It has been shown that nicotine improves working memory, executive function, and cognitive performance, both in human and animals (Rushforth et al, 2011 ; Jansari et al, 2013 ; Vafaee et al, 2015 ; Majdi et al, 2017 ). Nicotine also reduces reactive oxygen species (ROS) generation by brain mitochondria and prevents oxidative stress in a dose-dependent manner (Cormier et al, 2003 ; Guan et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%